2021
DOI: 10.6018/cpd.443591
|View full text |Cite
|
Sign up to set email alerts
|

Percepción del autoconcepto físico en estudiantes universitarios en tiempos de confinamiento por COVID-19

Abstract: El confinamiento por la COVID-19 ha ocasionado diversos cambios sociales, pero se desconoce su impacto en el autoconcepto físico. El presente trabajo tuvo por objetivo analizar la percepción del autoconcepto físico en estudiantes universitarios en tiempos de confinamiento por COVID-19. Se aplicó el cuestionario de autoconcepto físico Physical Self Questionnaire a estudiantes universitarios. Para la selección de la muestra se utilizó el procedimiento de muestreo aleatorio estratificado con un nivel de confianza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
5
2
0
2
Order By: Relevance
“…While the Physical-Medium Self-Concept and Physical-Negative Self-Concept groups are the least physically active, both groups are predominantly female and reflect a lower self-concept. In line with the findings of a study carried out during the pandemic [ 15 ], and showing a similar trend to that observed by Navas and Soriano [ 53 ] in their work prior to the pandemic. This could be attributed to social factors, such as stereotypes and prejudices that exist in the community [ 54 ], which generally affect women more than men.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…While the Physical-Medium Self-Concept and Physical-Negative Self-Concept groups are the least physically active, both groups are predominantly female and reflect a lower self-concept. In line with the findings of a study carried out during the pandemic [ 15 ], and showing a similar trend to that observed by Navas and Soriano [ 53 ] in their work prior to the pandemic. This could be attributed to social factors, such as stereotypes and prejudices that exist in the community [ 54 ], which generally affect women more than men.…”
Section: Discussionsupporting
confidence: 92%
“…While preventive measures that have been adopted in most countries of the world are fundamental in the fight against COVID-19, such as isolation including confinement or social distancing, while contributing to the distribution and care of cases that can be covered by the health system, it has also been argued that it may encourage sedentary behaviour, reduce regular physical activity or avoid daily activities, which increases the risk of developing diseases or worsening previous pathologies [ 13 ]. Therefore, several studies have been conducted to determine the real impact of confinement measures on physical activity in the university population [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…This was been confirmed in previous studies, which reported anxiety, depression and stress among the population [38]. Cadena-Duarte [39] (p. 50) stated that these confinement-related health issues may alter the perception of physical SC and psychological well-being. This influenced the development of behavioural, social and affective skills that consolidate through the interpersonal interaction process [37] since the possibilities of having physical contact, sharing ideas among groups, or learning collaboratively were reduced or disappeared, as well as other emotional aspects that are highly involved in body expression and communication.…”
Section: Covid-19 Pandemic and Pa Practicesupporting
confidence: 74%
“…The third line of argument to emerge from the present research pertains to the emotional component of nutrition in university students during confinement. Similar studies [ 36 , 37 ] have associated the lack of social interaction with peers, teachers, relatives, and friends with emotional instability in students. This factor emerged in the present research, which also proposed the novel factor of the “digitalisation of university teaching” as a catalyst of the aforementioned factor, potentially leading to an increase in stress, anxiety, and sleep disorders, alongside a reduction in self-esteem in students.…”
Section: Discussionsupporting
confidence: 53%